ASSESSMENT OF PSYCHIATRIC PATIENTS’ PERCEPTIONS, VIEWS, AND SATISFACTIONS WITH THE ROLES OF PHARMACISTS IN MENTAL HEALTH CARE – A STUDY IN A NIGERIA PSYCHIATRIC HOSPITAL - C, OFOR AMALA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: To assess the psychiatric patients’ perception, views, and satisfactions with the pharmacists’ role in mental health care. Methods: The study was conducted in a Neuropsychiatric Hospital in South Eastern part of Nigeria from October 2019 through January 2020 using a cross sectional survey in convenient samples and a total of 128 patients completed the study. The questionnaire contained the patients’ demographic details, six-item questions on respondents’ perception, 7-item questions on patients’ satisfaction, and six-item questions on the respondents’ view. The questionnaire was coded, checked for accuracy and analyzed using statistical package for social sciences version 23 for windows. Results: The response rate was 94% where 136 respondents showed willingness to participate, but 128 respondents completed the study. All the participants were young adults and adults, male (53.1%), female (46.9%). About 93.8% of the respondents agreed that the pharmacists were friendly and 89.1% admitted that pharmacists’ care were about perfect. About 69.5% were satisfied with the pharmacists’ professional outlook, while only 42.2% are of the view that the pharmacists offer counseling without their asking for it. Conclusion: The patients’ perception on the pharmacists’ skills and knowledge in handling psychiatric patients was high; their satisfaction with the pharmacists’ professional outlook can be considered fair, while their views on pharmacists’ counseling can be considered to be generally poor.